Central Nervous System Fungal Infections in Children With Leukemia and Undergoing Hematopoietic Stem Cell Transplantation: A Retrospective Multicenter Study. Issue 8 (25th November 2022) - Karaman, Serap; Kebudi, Rejin; Kizilocak, Hande; Karakas, Zeynep; Demirag, Bengu; Evim, Melike S.; Yarali, Nese; Kaya, Zuhre; Karagun, Barbaros S.; Aydogdu, Selime; Caliskan, Umran; Ayhan, Aylin C.; et al.
Abstract : Background: Central nervous system fungal infections (CNSFI) are seen in patients with hematologic malignancies and have high morbidity and mortality. Because of their rarity, there is limited data on CNSFI in children with no established treatment protocols or guidelines. Materials and Methods: In this multicenter retrospective study, 51 pediatric patients with leukemia, 6 of whom had undergone bone marrow transplantation, with proven or probable CNSFI were evaluated. Fungal infections were defined as proven or probable based on European Organisation for Research and Treatment of Cancer criteria. Proven CNSFI was diagnosed by appropriate central nervous system (CNS) imaging or tissue sample findings in combination with positive microbiological results of cerebrospinal fluid. A positive culture, microscopic evidence of hyphae, a positive result of the galactomannan assays are defined as positive microbiological evidence. Probable CNSFI was defined as appropriate CNS imaging findings together with proven or probable invasive fungal infections at another focus without CNS when there is no other explanatory condition. Data was collected by using the questionnaire form (Supplemental Digital Content 1, http://links.lww.com/JPHO/A541 ). Results: Seventeen patients had proven, 34 patients had probable CNSFI. Headaches and seizures were the most common clinical findings. The median time between the onset of fever and diagnosis was 5 days. The most common fungal agent identified was Aspergillus . Sixteen patients received single-agent, 35 received combination antifungal therapy. Surgery was performed in 23 patients. Twenty-two patients (43%) died, 29 of the CNSFI episodes recovered with a 20% neurological sequelae. Conclusion: CNSFIs should be considered in the differential diagnosis in patients with leukemia and refractory/recurrent fever, headache, neurologicalocular symptoms, and a radiologic-serological evaluation should be performed immediately. Early diagnosis and prompt management, both medical and surgical, are essential for improving clinical outcomes.